2003
DOI: 10.1136/bmj.326.7394.845
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive diseases of pregnancy and risk of hypertension and stroke in later life: results from cohort study

Abstract: Objective To examine the association between hypertensive diseases of pregnancy (gestational hypertension and pre-eclampsia) and the development of circulatory diseases in later life. Design Cohort study of women who had pre-eclampsia during their first singleton pregnancy. Two comparison groups were matched for age and year of delivery, one with gestational hypertension and one with no history of raised blood pressure. Setting Maternity services in the Grampian region of Scotland. Participants Women selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
394
7
20

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(438 citation statements)
references
References 23 publications
17
394
7
20
Order By: Relevance
“…Other studies report more inconsistent, conflicting, or negative results, with no association between GH alone and CVD for nonblacks after stratifying by race,5 with a positive association between GH and CVD but not for thromboembolic events (deep venous thrombosis or pulmonary embolism),27 and lack of positive association between GH and CVD 28. Compared with our study, these studies had limitations in terms of small population size and relatively short follow‐up for cardiovascular events 25, 26, 27, 28…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Other studies report more inconsistent, conflicting, or negative results, with no association between GH alone and CVD for nonblacks after stratifying by race,5 with a positive association between GH and CVD but not for thromboembolic events (deep venous thrombosis or pulmonary embolism),27 and lack of positive association between GH and CVD 28. Compared with our study, these studies had limitations in terms of small population size and relatively short follow‐up for cardiovascular events 25, 26, 27, 28…”
Section: Discussioncontrasting
confidence: 71%
“…A possible relationship between GH and risk of maternal CVD has been studied to a much smaller extent. While several studies have reported a significant association between GH and subsequent CVD,5, 19, 20, 23, 24, 25, 26, 27, 28, 29, 30 only 4 of these had a comparable cohort size and a similar follow‐up time compared with our study 19, 20, 23, 29. None of these studies looked at the combined effects of GH, SGA infant, preterm delivery, and parity as predictors of subsequent CVD.…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, it has been clearly shown that preeclampsia places women at long-term risk for CV diseases and that careful follow-up and aggressive preventive strategies are recommended. [32][33][34] For example, a meta-analysis which includes 43 million women and almost 200 00 women with preeclampsia showed that women who had preeclampsia are 2.7 times more likely to develop hypertension, and almost twice more likely to have ischemic heart disease, stroke or venous thromboembolism. 34 …”
Section: Hormone Replacement Therapy and Bpmentioning
confidence: 99%
“…1,[3][4][5] Although little is known about the pathophysiology of gestational hypertension, studies have shown that it is associated with features of the metabolic syndrome 6 and with later development of essential hypertension and cardiovascular disease. 7,8 This suggests that these conditions may have similar pathological mechanisms.…”
Section: Introductionmentioning
confidence: 97%